2013
DOI: 10.9790/0853-1064043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Bleeding Time And Clotting Time Among Gender Difference And Varying Blood Groups In UG Medical Student

Abstract: Blood group plays a vital role in the field of medicine. There is a clear association between ABO blood group status and von Willebrand factor. Deficiency of vWF leads to Hemorrhagic disorders, while elevated levels are a risk factor for thrombosis. Earlier studies state that the O group individuals have prolonged bleeding time and clotting time. The objective of this study was to assess the relationship between Bleeding time and clotting time among various Blood groups and also to identify any gender differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…This result was similar to those obtained by Kaur et al 17 where prolonged clotting time were more common among females but did not have any statistical significance. Studies done by Baishya et al, 18 Mondal et al 22 and Sasekala et al 23 found both bleeding time and clotting were found to be significantly higher in females compared to males.…”
Section: Resultsmentioning
confidence: 88%
“…This result was similar to those obtained by Kaur et al 17 where prolonged clotting time were more common among females but did not have any statistical significance. Studies done by Baishya et al, 18 Mondal et al 22 and Sasekala et al 23 found both bleeding time and clotting were found to be significantly higher in females compared to males.…”
Section: Resultsmentioning
confidence: 88%